Analysis of Impact of Urbanization on Environmental Quality in China. Issue 2 (March 2017) - Wei, Houkai; Zhang, Yan
Abstract: As a developing country with great regional disparities, China's rapid urbanization has had important impacts on environmental quality. In this study, the drivers‐mechanisms‐effects (DME) model is built, which shows how element agglomeration, scale growth, knowledge accumulation and industry evolution drive the environmental system to change during the urbanization process. An econometric regression model using provincial panel data is further constructed to empirically analyze the impacts of urbanization on environmental quality. It is shown that during the process of urbanization in China, element agglomeration and knowledge accumulation help to improve environmental quality but with weak positive effect, while growing urban scale and industrial structure have obvious negative effects on environmental quality. The "inverted‐U shape" (up first and then down) change in the environmental quality during China's urbanization process is obvious. It is critical that China concentrates on the transformations of both city development paths and urbanization models to reduce resource and environmental costs as much as possible.